1995
DOI: 10.1164/ajrccm/152.4_pt_2.s4
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of Human Respiratory Virus Infections

Abstract: Acute respiratory infections are the most frequent illnesses of the human host. Most infections are caused by viruses and bacteria; the proportion caused by viruses is much greater. The viruses most frequently involved are adenoviruses, influenza viruses, parainfluenza viruses, respiratory syncytial viruses, and rhinoviruses. Acute respiratory infections are more common in young children, have rather specific seasonal occurrences, and some agents are associated with specific respiratory syndromes. Risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 32 publications
2
98
2
Order By: Relevance
“…More importantly, pathology follow-up surveillance data during 18 months after the parainfluenza virus infection revealed that 32% of the lung transplant recipients developed active bronchiolitis obliterans (OB) (13). The median time between the parainfluenza virus infection and the development of OB was 6 months (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This is a very important finding because OB is considered the single most important limitation to long-term survival after lung transplantation with an incidence of 41% to 63% at 5 years post-transplant (31).…”
Section: Allograft Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, pathology follow-up surveillance data during 18 months after the parainfluenza virus infection revealed that 32% of the lung transplant recipients developed active bronchiolitis obliterans (OB) (13). The median time between the parainfluenza virus infection and the development of OB was 6 months (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This is a very important finding because OB is considered the single most important limitation to long-term survival after lung transplantation with an incidence of 41% to 63% at 5 years post-transplant (31).…”
Section: Allograft Complicationsmentioning
confidence: 99%
“…The spectrum of the disease in children ranges from a mild cold to croup, bronchiolitis and viral pneumonia. In adults these infections are usually mild and restricted to the upper respiratory tract (5). However, recent studies of the viral etiology of acute lower respiratory tract infections in adults indicate that parainfluenza virus accounts for 2.5 to 11.5% of hospitalized adult patients (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Human rhinoviruses are the most common viral infectious agents in humans (9). In the United States, rhinoviruses account for more than one billion cases annually of viral respiratory tract infections (VRTI; i.e., the common cold) (34).…”
mentioning
confidence: 99%
“…In some samples, a common wildtype respiratory virus (RSV, PIV1, PIV2, PIV3, influenza A or B virus, enterovirus, HRV, or adenovirus) was identified as a probable etiologic agent; however, no viruses were detected in more than three quarters of illness samples. Although most respiratory illnesses are caused by viruses (6), some of these illnesses may be caused by other pathogens, such as Streptococcus pyogenes, Mycoplasma pneumoniae, Streptococcus pneumoniae, nonencapsulated Haemophilus influenzae, Chlamydia pneumoniae, and Moraxella catarrhalis.…”
mentioning
confidence: 99%